APPLICATION OF MODULAR TEACHING TECHNOLOGY IN UNIVERSITY COURSE OF ARMENIAN LANGUAGE (Education in the 21st Century, 2022)
The article discusses the application of modular teaching technology in the university course of the Armenian language, consistently reveals the features, rules and principles of the modular teaching technology. The purpose of the study is to methodologically substantiate the effectiveness of the application of the modular teaching technology in a university course, focusing on the problems and difficulties that arise during teaching. As a result of the study, three key components of modular lessons have been revealed: a target action plan, a presentation of the material, and methodical guidelines regulating the educational process. The role of modular lessons in the formation and development of cognitive skills of students has been emphasized.The purpose of the development of modules is to divide the content of each topic of the course into components, to identify different forms and types of courses for each component, to coordinate them over time and to integrate with identifying the level of knowledge and skills of students for each module.As a result of the application of modular learning technology, the student approaches the learning process consciously and meaningfully, focusing on the strengths and weaknesses of his knowledge and skills.As  a result the student’s cooperation skills are developed,  the value of self-control and self-esteem increases. The application of modular teaching technology is aimed at the implementation of psychological and pedagogical diagnostics of the personality of students, the development and the improvement of the educational process through comprehensive methodological work.Using an example of a modular lesson on verb teaching presented in the university course of the Armenian language, the steps have been shown that lead students from explanatory teaching to active teaching with the application of the modern technologies and methods, in which the student becomes an active subject of the educational process, and the result of the course is an ability to find and apply the necessary information with the purpose of independent acquisition of knowledge.
Keywords: modular learning technology; modular lesson; modern learning technology; modern teaching methods; module; teaching grammar